The mediation role of Information Technology between Artificial Intelligence and Modern Accounting: Opportunities and Challenges - Bryar Sami Abdulrahman; Sardar Jalal Braim (QALAAI ZANIST JOURNAL, 2024)
The aim of this research is to examine and assess the mediator role of information technology (IT) in the amalgamation of artificial intelligence (AI) and contemporary accounting methodologies. The present study employed a quantitative research design to investigate the mediating role of information technology in the relationship between artificial intelligence (AI) and contemporary accounting practices. The study aims to include a sample size of 138 participants from different private businesses in Erbil. The findings revealed that the reliability of information technology mediates the relationship between artificial intelligence and modern accounting, accordingly, the first research hypothesis was supported. Moreover, it was found that the consistency of information technology mediates the relationship between artificial intelligence and modern accounting, accordingly, the second research hypothesis was supported. Lastly, it was found that the relevance of information technology mediates the relationship between artificial intelligence and modern accounting, accordingly, the third research hypothesis was supported. In order to effectively leverage the capabilities of artificial intelligence (AI) in contemporary accounting practices, it is imperative to establish a strong collaborative relationship between the information technology (IT) and accounting departments.